2016
DOI: 10.3892/ol.2016.4188
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length assessment in leukocytes presents potential diagnostic value in patients with breast cancer

Abstract: Abstract.Telomere shortening is associated with cancer development, primarily through the induction of genomic instability. The majority of studies have indicated that individuals with shorter blood telomeres may be at a higher risk of developing various types of cancer. There is increasing evidence that the study of the alterations in telomere length may improve cancer prognosis. The aim of the present study was to verify the use of telomere length parameters in the diagnostics of breast cancer stage. Telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
(34 reference statements)
3
14
0
Order By: Relevance
“…Our current findings, suggesting that the number of consecutive nights is important in telomere shortening, is interesting in light of previous published data demonstrating increased breast cancer risk only in nurses that had worked a minimum of six consecutive nights for at least 5 years . Thus, while telomere shortening contributes to tumor progression and is generally associated with increased cancer risk , an association with breast cancer risk is inconclusive, as contradicting results on TL and breast cancer risk have been reported . In line with several previous studies , we here observed no differences in TL in cases and controls and no association with breast cancer risk when disregarding night work.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our current findings, suggesting that the number of consecutive nights is important in telomere shortening, is interesting in light of previous published data demonstrating increased breast cancer risk only in nurses that had worked a minimum of six consecutive nights for at least 5 years . Thus, while telomere shortening contributes to tumor progression and is generally associated with increased cancer risk , an association with breast cancer risk is inconclusive, as contradicting results on TL and breast cancer risk have been reported . In line with several previous studies , we here observed no differences in TL in cases and controls and no association with breast cancer risk when disregarding night work.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, while telomere shortening contributes to tumor progression and is generally associated with increased cancer risk , an association with breast cancer risk is inconclusive, as contradicting results on TL and breast cancer risk have been reported . In line with several previous studies , we here observed no differences in TL in cases and controls and no association with breast cancer risk when disregarding night work. However, when evaluating the TL in cases and controls working night shifts, significantly shorter TLs were observed in cases than controls working four consecutive night shifts for more than 5 years.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…9-12,18,20 Short LTL associated with an increased risk of developing oral premalignant lesions (OPL) and oral squamous cell carcinoma (OSCC), suggesting that patients with OPL and short LTL have an increased risk to progress to OSCC. 22 By contrast, in two other studies, 20,23 the TL was shorter in leukocytes from patients with HNSCC compared to healthy controls. 20 It was also suggested that TL influenced the malignant progression of preneoplastic lesions of the oral cavity.…”
Section: Discussionmentioning
confidence: 73%